Complex regional pain syndrome (CRPS), a review - Castillo Guzmán, Sandra; Nava Obregón, Teresa Adriana; Palacios Ríos, Dionicio; Estrada Cortinas, Javier Ángel; González García, M. C.; Méndez Guerra, Jesús Francisco; González Santiago, Omar (UANL. Facultad de Medicina, 2015)
Complex regional pain syndrome is a chronic and painful condition that affects the quality of life of patients. It is usually triggered by a traumatic event of the soft tissues involving the nervous tissue. Although the factors that cause the syndrome are varied and not well known, different etiopathologic concepts have been proposed to explain the presence of this syndrome, such as autonomic dysfunction and changes in CNS plasticity, among others. The patient characteristically presents pain, sensory abnormalities, vasomotor disturbances in the skin, edema, changes in sweating, and motor alterations. The pain is associated with changes in the autonomic nervous system and has a distal predominance. Since there is no definitive diagnostic test, diagnosis is mainly based on a complete medical history and physical examination. Treatment is multidisciplinary and based on pain relief. Although in most cases evolution is favorable, rapid diagnosis and treatment are recommended to avoid dystrophic stage as much as possible